2011
DOI: 10.1002/pbc.23387
|View full text |Cite
|
Sign up to set email alerts
|

Risk‐adapted therapy for infantile myofibromatosis in children

Abstract: Infantile myofibromatosis is a rare soft tissue tumor mainly concerning infants. Surgery is the treatment of choice for solitary forms when excision is possible. Close follow-up may be proposed in the case of inoperable sites. In multicentric life-threatening forms, chemotherapy promotes tumor regression and the vinblastine and methotrexate combination is effective with few long-term adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 44 publications
0
58
0
1
Order By: Relevance
“…The pathologic differential diagnosis includes IM, desmoplastic fibromas, low-grade fibrosarcomas, fibrous dysplasia, and nonossifying fibromas 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathologic differential diagnosis includes IM, desmoplastic fibromas, low-grade fibrosarcomas, fibrous dysplasia, and nonossifying fibromas 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Of the 39 cases, 24 had osseous involvement, but there were no recorded cases of CGF with only osseous involvement 4 . In a more recent review, Levine et al summarized 30 cases of multicentric IM with or without visceral involvement 6 . Review of these cases revealed only 1 in which involvement was only osseous; all others cases had lesions that involved skin and soft tissue or organs 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This entity, defined by a benign proliferation of fibroblasts and myofibroblasts, is subdivided into solitary and multicentric forms that may or may not have visceral involvement (Dishop and Kuruvilla 2008). The median age of presentation is 5 months for multicentric forms and 26 months for solitary forms (Levine et al 2012). Myofibromas usually appear as a demonstrates a large, well-circumscribed, high signal intensity mass (asterisk) compressing the adjacent lung and everting the diaphragm, with associated ascites related to inferior vena cava compression mass with a thick-wall and a hypoechoic or anechoic center on ultrasound, and can demonstrate peripheral calcifications and adjacent bony erosion on CT. On MRI, they are usually hypointense on T1-weighted images and hyperintense with variable central hypointensity on T2-weighted images, and exhibit peripheral contrast enhancement (Koujok et al 2005) (Fig.…”
Section: Infantile Myofibromatosismentioning
confidence: 98%
“…Pulmonary masses may be a manifestation of multicentric visceral involvement and should not be misinterpreted as metastatic disease. Multicentric myofibromatosis with visceral involvement is associated with high morbidity and mortality despite chemotherapy and surgery, while the prognosis is excellent in other forms with surgery alone (Levine et al 2012). …”
Section: Infantile Myofibromatosismentioning
confidence: 99%